2021
DOI: 10.1029/2021ef002064
|View full text |Cite
|
Sign up to set email alerts
|

Borderless Heat Hazards With Bordered Impacts

Abstract: Heatwaves are as impactful as other hazards, such as floods, but reporting their characteristics and impacts, as well as understand their risk is challenging because they are an invisible physical phenomenon (Brimicombe et al., 2021). They are also considered to be widely underreported in official databases, reports, and in news media (Harrington & Otto, 2020;Khare et al., 2015). However, robust reporting is essential not only for communicating the risk of heatwaves, but also to develop effective policy and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Impact‐based forecasting, complementing forecasts with impact estimates such as expected damage and human consequences, can provide important advantages for decision‐making (Merz et al ., 2020), and recognising heat stress as a physiology‐mediated effect of compound environmental factors could open the pathway to human‐centric weather forecasting (Di Napoli et al ., 2021). Alongside trends in extreme temperature, studies have also shown that areas impacted by heat stress have grown (since 2000, Brimicombe et al ., 2021), and with increasing populations exposed to heat stress during heatwaves, it is imperative to consider biometeorological forecasts. This can be particularly meaningful in regions, like Canada, where local populations, due to lower exposure to hot summer conditions, could have more difficulty in physiologically adapting to heat extremes when they occur (Bassil et al ., 2007).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact‐based forecasting, complementing forecasts with impact estimates such as expected damage and human consequences, can provide important advantages for decision‐making (Merz et al ., 2020), and recognising heat stress as a physiology‐mediated effect of compound environmental factors could open the pathway to human‐centric weather forecasting (Di Napoli et al ., 2021). Alongside trends in extreme temperature, studies have also shown that areas impacted by heat stress have grown (since 2000, Brimicombe et al ., 2021), and with increasing populations exposed to heat stress during heatwaves, it is imperative to consider biometeorological forecasts. This can be particularly meaningful in regions, like Canada, where local populations, due to lower exposure to hot summer conditions, could have more difficulty in physiologically adapting to heat extremes when they occur (Bassil et al ., 2007).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…They often coincide with other natural hazards (e.g. wildfires and droughts), and due to climate change, are increasing in intensity, duration and frequency (Perkins‐Kirkpatrick and Gibson, 2017; Brimicombe et al ., 2021). Not only are more intense extremes projected with future climate change, but also events such as the one discussed here, that break records by much larger margins, and their probability of occurrence depends strongly on the rate, rather than amount, of global warming (Fischer et al ., 2021).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Limitations of this method are that there are biases and under-reporting of hazards by this database (Brimicombe et al, 2021a;Gall et al, 2009). In addition, this database only includes hazards that are considered a disaster, where an agency declares a state of emergency, or where it is reported that over 100 people have been affected(CRED, 2020).…”
Section: Heat Wave 38mentioning
confidence: 99%
“…In addition, this database only includes hazards that are considered a disaster, where an agency declares a state of emergency, or where it is reported that over 100 people have been affected(CRED, 2020). However, it remains the most comprehensive source of reported weather hazards (Brimicombe et al, 2021a;Gall et al, 2009).…”
Section: Heat Wave 38mentioning
confidence: 99%
See 1 more Smart Citation